2006
DOI: 10.2164/jandrol.05064
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Neutral α‐Glucosidase Activity in Human Semen

Abstract: ABSTRACT:Although there are contradictory reports, the biochemical evaluation of the seminal activity of neutral ␣-glucosidase (NAG) has repeatedly been described as an important parameter to test epididymal patency and is recommended by the WHO. Because, for a number of diagnostic parameters, seasonal variations have been described even in the human, it was the aim of this study to investigate possible circannual changes of NAG. This is an important aspect of andrological diagnosis, as seasonal changes of spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…The pH increase noted within A2 subgroup could be related to the low seminal level of NAG and the increase level of aromatase mRNA. It has been demonstrated that pH was correlated positively with seminal activity of alpha‐glucosidase and negatively with citric acid (Obidoa et al ., ; Henkel et al ., ; Said et al ., ). Alterations of sperm motility cover multiple origins and the combination of additional tests such as aromatase transcripts, neutral alpha‐glucosidase, pH and vitality could bring new insights about the pathological causes of asthenospermic patients.…”
Section: Discussionmentioning
confidence: 98%
“…The pH increase noted within A2 subgroup could be related to the low seminal level of NAG and the increase level of aromatase mRNA. It has been demonstrated that pH was correlated positively with seminal activity of alpha‐glucosidase and negatively with citric acid (Obidoa et al ., ; Henkel et al ., ; Said et al ., ). Alterations of sperm motility cover multiple origins and the combination of additional tests such as aromatase transcripts, neutral alpha‐glucosidase, pH and vitality could bring new insights about the pathological causes of asthenospermic patients.…”
Section: Discussionmentioning
confidence: 98%
“…After a 3-month storage period, about 30-40% of the activity remained [Dias et al 2004]. Circannual changes in the NAG activity have also been documented [Henkel et al 2006]. Considering these practical concerns as well as the poor correlation noted between the NAG activity and sperm motility or morphology (Table 1), routine assessment of NAG may not be advisable.…”
Section: Discussionmentioning
confidence: 99%
“…2 Spermatogenesis is a temperature-dependent process, which scrotal temperature is kept lower than 2°C to 8°C of the core body temperature and regulated by a specialized blood supply. [13][14][15][16] The epididymis is the main source of carnitine in human seminal plasma. [3][4][5][6] Previous studies on sperm parameters, sperm apoptosis, oxidative stress, and molecular mechanisms have been reported.…”
Section: Introductionmentioning
confidence: 99%